2015
DOI: 10.1007/s12105-015-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

Sino-Orbital Osteoma With Osteoblastoma-Like Features

Abstract: An 18 year old male presented with worsening headaches, pain with ocular movement and swelling that involved the left anterior periorbital and frontal sinus region. Radiographic images revealed a polypoid bony mass of mixed radiodensity extending into the left and right frontal sinuses. Histologic examination of the resection material resulted in the diagnosis of an osteoma with osteoblastoma-like features, an osteoma variant that has zones indistinguishable from an osteoblastoma. The clinical, radiographic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…In children and adolescents, craniofacial osteomas tend to arise in the frontal or ethmoid sinuses at the junction between endochondral and membranous bones. According to the literature, nearly 40% of sino-orbital osteomas have histologic features similar to osteoblastomas (immature bone with enlarged osteoblasts and fibrovascular stroma); therefore, the term “sino-orbital osteoma with osteoblastoma like features” has been recommended [ 22 ]. Some authors have even suggested that probably many reported sino-nasal osteoblastomas are actually osteomas with osteoblastoma-like features [ 23 ].…”
Section: Primary Intraosseous Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In children and adolescents, craniofacial osteomas tend to arise in the frontal or ethmoid sinuses at the junction between endochondral and membranous bones. According to the literature, nearly 40% of sino-orbital osteomas have histologic features similar to osteoblastomas (immature bone with enlarged osteoblasts and fibrovascular stroma); therefore, the term “sino-orbital osteoma with osteoblastoma like features” has been recommended [ 22 ]. Some authors have even suggested that probably many reported sino-nasal osteoblastomas are actually osteomas with osteoblastoma-like features [ 23 ].…”
Section: Primary Intraosseous Tumorsmentioning
confidence: 99%
“…2 ). As opposed to osteomas, which typically present polypoid intraorbital or intrasinonasal growth, osteoid osteoma, which is exceptionally rare in the craniofacial bones, presents with a central nidus surrounded by a sclerotic peripheral zone [ 22 ]. Surgery via an endoscopic approach is the treatment of choice in large osteomas and osteoblastomas while small asymptomatic osteomas are followed clinically and with cross-sectional imaging.…”
Section: Primary Intraosseous Tumorsmentioning
confidence: 99%
“…Differential diagnosis on imaging includes osteoblastoma, which is also a benign tumor but malignant transformation into osteosarcoma was reported [ 8 , 9 ]. The pathological specimens in some reported osteoma cases suggested osteoblastoma-like lesions, and such entities were described as osteomas with osteoblastic features (OObF) [10] , [11] , [12] , [13] . OObF does not have a more aggressive and clinical course than osteoma, but it more likely extends into adjacent structures, such as the orbit or other paranasal sinuses [10] .…”
Section: Introductionmentioning
confidence: 99%
“… 23 Bilodeau et al 23 reported a case of mandibular cementoblastoma with histologic and radiographic features mimicking osteoblastoma and osteosarcoma. McCann et al 24 reported a case of craniofacial osteoma presenting with pain in the orbito-frontal region resembling sinusitis. Radiographically, the lesion appeared as a mixed radiodensity expansile entity with ground-glass fibro-osseous-like features in the frontal sinus, closely resembling the features of the present case, and the final histologic diagnosis was osteoblastoma with osteoblastoma-like features.…”
Section: Discussionmentioning
confidence: 99%